A VAR Analysis for the Growth Regime and Demand Formation Patterns of the Japanese Economy - Hiroshi Nishi (Revue de la Régulation)
This study examines the income distribution and demand formation pattern of the Japanese economy using the VAR model. The post-Keynesian model is used for theoretical reference. The VAR model in this paper includes income distribution, consumption growth rate, export demand, GDP, and capital accumulation. The results of this study indicate that between 1985 and 2008, the profit-led demand formation pattern was dominant in the Japanese economy. In this regime, both domestic and external demands have a positive relationship with GDP growth. In the bubble period, favourable macroeconomic performance was sustained by active consumption and investments realized from the rise in asset prices and improvement in economic outlook. However, after the bubble burst, a rise in wage share did not maintain consumption demand, and investment demand stagnated due to the deterioration of profitability, stock adjustments, and a credit crunch. Hence, the Japanese economy has failed to realize a domestic demand-led growth sincethe 1990s. After 2002, export demand expanded and profit share recovered, which induced investment expansion. Consequently, there was an improvement in the Japanese macroeconomic performance, led by external demand, until the subprime shock occurred.